Leisure Activities and Rural Community Change: Valuation and Use of Rural Space among Permanent Residents and Second Home Owners. Issue 2 (4th November 2013) - Pitkänen, Kati; Adamiak, Czesław; Halseth, Greg
Abstract Rural communities are getting more diversified in terms of people's backgrounds, sources of livelihood and interests towards the rural landscape. A common way to discuss rural community change has been to contrast in‐migrants and seasonal residents with long‐term rural residents. In this article, we aim to challenge this segmentation. We ask what it is to be a dweller in the modern countryside and how much the residential status has to do with people's interests and use of space. Based on a postal survey in a case study area in Finland, we look into the differences in the valuation of different leisure activities performed in rural space between second home owners and permanent residents. After dividing permanent residents and second home owners into further subgroups based on their spatial and temporal possibilities to engage in rural leisure, we found that there are no specific activities or groups of activities typical for certain groups of rural leisure space users. Differences between local residents and second‐home owners are rarely explained by this simple dichotomy, rather the differences are better explained by spatial and temporal accessibility.